ChemInform Abstract: Organocatalytic Michael Addition/Intramolecular Julia—Kocienski Olefination for the Preparation of Nitrocyclohexenes. Issue 15 (15th April 2014) - Rodrigo, Eduardo; Garcia Ruano, Jose Luis; Cid, M. Belen
Abstract Application of this method is demonstrated by the formal total synthesis of Trandolapril (VIII).